Solid Water Melt Dominates the Increase of Total Groundwater Storage in the Tibetan Plateau. Issue 18 (20th September 2022) - Zou, Yiguang; Kuang, Xingxing; Feng, Yuqing; Jiao, Jiu Jimmy; Liu, Junguo; Wang, Can; Fan, Linfeng; Wang, Qingjing; Chen, Jianxin; Ji, Fang; Yao, Yingying; Zheng, Chunmiao
Abstract: Understanding how groundwater storage (GWS) responds to climate change is essential for water resources management and future water availability in the Tibetan Plateau (TP). However, the dominant factor controlling long‐term GWS changes remains unclear and its responses to climate change are not well understood. Here we combined multi‐source datasets including in‐situ measurements, satellite observations, global models, and reanalysis products to reveal that GWS increased at 5.59 ± 1.44 Gt/yr during 2003–2016 while showing spatial heterogeneities with increasing trends in northern TP and glacial regions and declining trends in central and southern TP. The accelerated transformation from solid water (glaciers, snow, and permafrost; −17.72 ± 1.53 Gt/yr) into liquid water provide more recharge to groundwater, dominating the total GWS increase. This study contributes to a better understanding of the hydrological cycle under climate change and provides key information for projecting water availability under different future scenarios in the TP. Plain Language Summary: Long‐term groundwater storage (GWS; the amount of water stored in the pores, fissures, and caves of soil and rocks within the underground saturated zone) changes in response to climate change in the Tibetan Plateau (TP), and its dominant controlling factor has not been fully understood. There are very limited observation wells in the TP to monitor the groundwater level changes. This study used satellite observations, modeling, and reanalysis data to investigate GWS changes in the TP during 2003–2016. Results show that the GWS increased by 5.59 ± 1.44 Gt/yr during this period. The accelerated climate warming on the TP has led to significant solid water melt, including glacier melt, snow melt, and permafrost thaw. The solid water storage showed a decreasing trend (−17.72 ± 1.53 Gt/yr) and provided more water to infiltrate to recharge groundwater. The solid water melt has been identified to be the dominant source of GWS increase in the TP. The results of this study will help us to better understand the changes in the water cycle on the TP caused by climate change. Key Points: Multiple satellite observations, modeling, and reanalysis data were used to reveal groundwater storage changes in the Tibetan Plateau Groundwater storage increased (5.59 ± 1.44 Gt/yr) in the entire Tibetan Plateau from 2003 to 2016 Declining solid water (−17.72 ± 1.53 Gt/yr) including glaciers, snow, and permafrost dominates increasing groundwater storage